Amelioration of dextran sodium sulphate-induced colitis in mice by treatment with Lactobacillus rhamnosus and Lactobacillus reuteri: intraspecific and interspecific patterns - Chunxiu Lin; Yuxing Zheng; Bo Zhang; Guopeng Lin; Kexin Shang; Jianxin Zhao; Gang Wang; Wei Chen (Food Science and Human Wellness)
Lactobacillus rhamnosus (Rh) and Lactobacillus reuteri (Re) are well-known probiotic species in inflammatory bowel disease (IBD) research. The variations between these species’ efficacy against colitis, and their model of action in this regard, are intriguing and enable treatment to be individually tailored to patients. In this study, four strains each of Rh and Re were isolated from fecal samples and their draft genomes were sequenced. The anti-colitis activities of both strains involved various aspects of intestinal immune, physical, chemical, and biological barrier function. Strikingly, the tested strains exhibited considerable interspecies and intraspecies specificity in colitis amelioration. Rh strains significantly outperformed Re strains in terms of short-chain fatty acid synthesis. Nevertheless, Re strains were more effective than Rh strains in inhibiting production of inflammatory factors; promoting production of intestinal mucus, antimicrobial peptides, and tight junction proteins; and supporting the stem cell compartment. This accounts for the anti-colitis outcomes of Re strains being superior to those of Rh strains. In addition, the effective Rh and Re strains were found to express high concentrations of specific carbohydrate metabolism- and prophage-related genes, respectively. Taken together, the results of this study could assist researchers in developing effective therapies for IBD.